Loss of dynamin 1-like protein impairs mitochondrial function and self-renewal, and activates the integrated stress response in human embryonic stem cells - Cieslar-Pobuda, Artur; Caglayan, Safak (Frontiers in Genetics, 2025)
Dynamin 1-like protein (DNM1L/DRP1) is a crucial regulator of mitochondrial fission in cells and pathogenic mutations in DNM1L are linked to developmental and metabolic disorders in humans. While the role of DNM1L has been described in patient-derived fibroblasts, its function in early human development remains unclear. In this study, we generated DNM1L deficient human embryonic stem cells (hESCs) using CRISPR/Cas9 to investigate the consequences of DNM1L deficiency and impaired mitochondrial fission on stem cell function. DNM1L−/− hESCs exhibited hyperfused mitochondrial networks, reduced mitochondrial membrane potential, and elevated oxidative stress, indicating compromised mitochondrial fitness. Functionally, DNM1L−/− hESCs showed diminished self-renewal, and reduced expression of the core pluripotency factor OCT4, while NANOG expression was unaffected. We further found that differentiation potential toward the early ectodermal lineage was impaired, whereas early endodermal and mesodermal differentiation remained intact. Notably, integrated stress response (ISR) pathway was activated in DNM1L−/− hESCs, as shown by increased phosphorylated eIF2a and upregulation of downstream targets including activating transcription factor 4 (ATF4), ATF3, ATF5, and DDIT3. Restoring DNM1L expression by reintroduction of DNM1L into the AAVS1 locus rescued mitochondrial morphology and function, normalized ISR activation, and restored self-renewal and OCT4 expression in DNM1L−/− hESCs. These findings demonstrate that DNM1L is essential for maintaining mitochondrial homeostasis, stress response, self-renewal, and pluripotency in hESCs, and emphasize the importance of mitochondrial fission in stem cell function.